(untitled) (Global Journal of Management and Business Research, 2015)
Today we live in conditions of constant struggle for achieving financial power which enables dominance of the negative power and influence over the lives of others. This leads to destruction of the moral, ethical and other value norms alike, and the life in the organization becomes a place where we are seen through the prism of material asset. A world dominated by financial capital does not know the individual life values.